THE LANGUAGE STYLE IN THE LYRICS OF DARA AYU'S SONG AND ITS LEARNING IMPLICATIONS - Anwar, Syamsul; Nirmala, Afsun Aulia (Universitas Hamzanwadi, 2020)
Literature is an art form expressed by human thoughts and feelings with the beauty of language, the authenticity of ideas, and the depth of messages. instruction